Fluxnet Archive Product from Halsingfors mire, 2020–2023 - Matthias Peichl (Integrated Carbon Observation System, 2026)
Archive Product for Ecosystem Measurements. Fluxes, Meteo and ancillary measurements processed with the International standard FLUXNET procedure (ONEFlux suite) with different time aggregations.
Peichl, M. (2026). Fluxnet Archive Product from Halsingfors mire, 2020–2023, FLUXNET, https://hdl.handle.net/11676/d2E6mfPz9El6AVmc8bV_2xnA
Keywords: Ecosystem Thematic Centre; carbon flux; meteo; none-ICOS; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Physical Geography; Naturgeografi; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap